A Low-Cost IoT Platform for Heat Stress Monitoring in Dairy Cattle - Choquehuanca-Zevallos J.J. (2021)
This research has been funded by CONCYTEC Project–World Bank, contract number 017-2018-FONDECYT-BM-IADT-MU